ANALISIS PENGARUH KUALITAS LAYANAN APLIKASI MOBILE BANKING DAN PRODUK BANK TERHADAP KEPUASAN NASABAH UNITED OVERSEAS BANK INDONESIA DI BATAM - Octavia, Ecca Yolanda; Arnomo, Sasa Ani (LPPM Universitas Putera Batam, 2023)
Bank services in physical or non-physical service clould be another strategy to win the attention of customer. The satisfaction from the customers is very highly important to establish since the industry is very competitive. UOB Bank is one of the private banks in Batam city that provide mobile banking application which called TMRW and it has several bank products like housing credit, credit cards, deposit and other financial product as well. Research here is conducted to explore the effect of the mobile application of the UOB called TMRW along with the product tha effect satisfaction of the customer. The researcher took random sample in this case with the regresseion method for the hypthesis test. The result of the researh showed the profile of the responden averagely has minimum 2 bank product on their possesion and 100% using the TMRW application. The Regression showed that partially the qualitity of the mobile application TMRW has effects to the customers satisfaction, the variabel of the Quality of bank product has effects for the customers satifaction. Simultaneously quality of the mobile app TMRW and Quality of the bank product has effects for the customers satisfaction